Competitive differential pricing. (2nd March 2021) - Chen, Yongmin; Li, Jianpei; Schwartz, Marius
Abstract: We analyze welfare under differential versus uniform pricing across oligopoly markets that differ in costs of service, and establish general demand conditions for differential pricing by symmetric firms to increase consumer surplus, profit, and total welfare. The analysis reveals why competitive differential pricing is generally beneficial—more than price discrimination—but not always, including why profit may fall, unlike for monopoly. The presence of more competitors tends to enlarge consumers' share of the gain from differential pricing, though profits often still rise. When firms have asymmetric costs, however, profit or consumer surplus can fall even with 'simple' linear demands.